Industrial training report: Universiti Sains Malaysia (USM) / Mohammad Ashraf Kamal - Kamal, Mohammad Ashraf (Perpustakaan Tengku Anis, 2016)
The purpose of this documentation is to report about the recently industrial training that had been started from 1st August 2016 until 3(1-h December 2016 in Pusat Pengetahuan Komunikasi & Teknologi and Hamzah Sendut Library at Universiti Sains Malaysia (USM) Pu/au Pinang under the supeNision of Mr. Adnan Bin Hamid as the Ketua Seksyen Pusat Pengetahuan Komunikasi & Teknologi. This documentation provide the details regarding all the activities that is done by the intern during the industrial training. The intern had been assigned with a special project which is to develop a new website for International Conference on Libraries (/COL) Website for Hamzah Sendut Library. The current website for the International Conference is not attractive and need to be change with a new website to make it more attractive and interactive. From the intern observation, all the evidence, opinions and recommendations are being included in this documentation.